(3cJGH aj GdZRh hGdLgGO (B( (3hJQJjH GddYH HGdQeM heG jJYdb Hg (B)s
(3ChdgG (B:s
(3CeG HYO , aGdZRh hGdLgGO ai SHjd Gddg JYGdi ef CaVd GdCYeGd s
(3eQJH Ydi (B72 (3HfOkG jdjg aUd ai (B" (3GdJSGQjM (B" (3Ke UaMGJ ai gPG GdehVY ef cJGH CNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ HGdgfO (B(3504) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs